2014
DOI: 10.1007/s10957-014-0654-z
|View full text |Cite
|
Sign up to set email alerts
|

Robust Optimal Control of a Microbial Batch Culture Process

Abstract: This paper considers the microbial batch culture process for producing 1,3-propanediol (1,3-PD) via glycerol fermentation. Our goal was to design an optimal control scheme for this process, with the aim of balancing two (perhaps competing) objectives: (i) the process should yield a sufficiently high concentration of 1,3-PD at the terminal time and (ii) the process should be robust with respect to changes in various uncertain system parameters. Accordingly, we pose an optimal control problem, in which both proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Here, on the basis of Eq. (10) and the method in [36,37], we obtain the result which is listed in Table 1.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, on the basis of Eq. (10) and the method in [36,37], we obtain the result which is listed in Table 1.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…However, that is often an invalid assumption, as parameters are subject to natural variability and uncertainties that are due to insufficient knowledge about the phenomenon under investigation. Similar to [36,37], we consider the system sensitivity with respect to the uncertain model parameters as follows:…”
Section: Optimal Control Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of batch culture with continuous and fed-batch cultures has recently been come into investigators notice throughout the world as it can obtain the highest production concentration and molar yield 1,3-PD to glycerol [1]. Not only the nonlinear dynamic behaviour of microorganisms has been the objective of a number of theoretical works, but also much modelling research on the process of batch culture has been reported recently in [2,16,23,28]. However, for all the papers mentioned above, the strong stability is not taken into consideration in batch culture.…”
Section: Introductionmentioning
confidence: 99%